2022
DOI: 10.4187/respcare.10140
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Among Respiratory Therapists in a Tertiary Hospital in Saudi Arabia

Abstract: Background: Respiratory therapists (RTs) provide various types of patient care in different clinical settings. Burnout can have an undesirable effect on RTs and their patients. Managing the COVID-19 pandemic, specifically in hospitals, could induce stress in RTs and increase the likelihood of burnout. Therefore, this study aimed to measure the level of burnout among RTs during the COVID-19 pandemic. Method: A validated cross-sectional questionnaire was used to identify the prevalence and characteristics of bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Using the sum method to calculate burnout prevalence, a total of 95% of RT students and interns experienced moderate to high burnout levels. As for the burnout subscales (EE, DP, and PA), participants had mean (SD) scores of 27 for EE (10), 11.7 for DP (7), and 31 for PA (8). In addition, 52% of the RT students and interns were emotionally exhausted, 59% indicated a high level of depersonalization, and 55% indicated a low level of personal accomplishment, as shown in Table 2.…”
Section: Prevalence Of Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the sum method to calculate burnout prevalence, a total of 95% of RT students and interns experienced moderate to high burnout levels. As for the burnout subscales (EE, DP, and PA), participants had mean (SD) scores of 27 for EE (10), 11.7 for DP (7), and 31 for PA (8). In addition, 52% of the RT students and interns were emotionally exhausted, 59% indicated a high level of depersonalization, and 55% indicated a low level of personal accomplishment, as shown in Table 2.…”
Section: Prevalence Of Burnoutmentioning
confidence: 99%
“…Recently, 79% of respiratory therapists reported burnout in a survey among 1114 respiratory therapists from 26 medical centers in the United States [ 6 ], mainly due to high patient morbidity and mortality as well as heavy workloads in the critical care units [ 6 ]. A recent cross-sectional study conducted in a tertiary hospital in Saudi Arabia also reported high levels of the three domains of burnout among RTs: 77% with emotional exhaustion, 98% with depersonalization, and 73% with low personal achievement [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies reported the risk factors of burnout [ 20 , 23–26 , 30 , 31 , 33 ]. Female pulmonologists or respiratory therapists tended to experience more burnout than their male counterparts [ 20 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported the risk factors of burnout [ 20 , 23–26 , 30 , 31 , 33 ]. Female pulmonologists or respiratory therapists tended to experience more burnout than their male counterparts [ 20 , 23 , 26 ]. In two studies, a heavier weekly workload was reported to exacerbate burnout [ 24 , 26 ], while another study presented that the weekly workload was not significantly associated with burnout [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a previous cross-sectional study conducted in the Southern region of Saudi Arabia, which included 95 physicians and 187 nurses working in different emergency departments, indicated that 88% of HCPs experienced emotional exhaustion. Another study, which included 66 respiratory therapists (RTs) working in a main tertiary hospital in the capital of Saudi Arabia, revealed that RTs experienced a significant level of burnout across the three dimensions: 77% with EE, 98% with DP, and 73% with low PA [8]. The exact cause of increased burnout is unknown, but factors such as years of experience, working in critical settings, staff shortage, and management support have been suggested.…”
Section: Introductionmentioning
confidence: 99%